2020
DOI: 10.1097/j.jcrs.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of manifest refraction

Abstract: Purpose: To evaluate the intraexaminer repeatability and the interobserver reproducibility of manifest refraction. Setting: Tertiary referral center. Design: Retrospective study. Methods: Patients attending at least 2 preoperative refractions before undergoing subsequent refractive surgery were included. All manifest refractions were performed by 1 of 4 experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
5
11
0
Order By: Relevance
“…Considering the agreement for subjective refraction, the difference in absolute value increased significantly with the measured spherical magnitude. Likewise, the difference in absolute value increased significantly with the measured cylinder magnitude, while the difference in axis decreased significantly with the measured cylinder magnitude 24 . We also observed a significant association in the differences for M, J 0 and J 45 power vectors across the three aberrometers as the power vector magnitude changed (Figure 2).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Considering the agreement for subjective refraction, the difference in absolute value increased significantly with the measured spherical magnitude. Likewise, the difference in absolute value increased significantly with the measured cylinder magnitude, while the difference in axis decreased significantly with the measured cylinder magnitude 24 . We also observed a significant association in the differences for M, J 0 and J 45 power vectors across the three aberrometers as the power vector magnitude changed (Figure 2).…”
Section: Discussionsupporting
confidence: 51%
“…Likewise, the difference in absolute value increased significantly with the measured cylinder magnitude, while the difference in axis decreased significantly with the measured cylinder magnitude. 24 We also observed a significant association in the differences for M, J 0 and J 45 power vectors across the three aberrometers as the power vector magnitude changed (Figure 2). The intrasession repeatability of aberrometers could be influenced by fluctuations in accommodation, tear film instability and micro eye movements.…”
Section: Discussionmentioning
confidence: 62%
“…This was also the first time anyone has deeply investigated the participants’ attitudes toward tele-controlled subjective refraction. In our cross-sectional study, we found no statistically significant differences between traditional subjective refraction and tele-controlled subjective refraction for any parameters, and the 95% limits of agreement between the 2 methods of refraction in the S (±0.42 D), C (±0.39 D), and SE (±0.36 D) were both similar to a previous study on reproducibility of subjective refraction (±0.44 D 16 for S, ±0.31 D 17 for C, and ±0.37 D to ±0.56 D 18 21 for SE). Researchers generally agree that the variation of refractive error should be at least ±0.50 D and consider this to be the minimum significant shift in a refractive state.…”
Section: Discussionsupporting
confidence: 84%
“…When considering this data, it is also important to consider that manifest subjective refraction is not perfect either, and it has a measurement noise of about 0.16 D as recently reported by Taneri et al . [ 19 ] The mean difference between manifest subjective refraction and wavefront-based objective refraction in our study falls well between this measurement noise of subjective refraction alone, which suggests even further that data obtained by both methods are very similar.…”
Section: Discussionsupporting
confidence: 77%